1974
DOI: 10.1103/physrevlett.32.212
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Phase-Dependent Conductivity in Superconducting Point Contacts

Abstract: Phys. Rev. Lett. _15, 964 (1965). 2 J. W. Halley, Phys. Rev. _181, 338 (1969). 3 M. J. Stephen, Phys. Rev. JJ37, 279 (1969). The analogous scattering in solid helium has been considered byThe total current density for a superconducting tunnel junction was calculated by Josephson 1 to be j =j e sine? + cr 0 (F, T)V+ a x (V 9 T)Vcos Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The ratio ε between the PDC and the leakage conductance has been investigated in a number of experiments on tunnel junctions [8,12], point contacts [9,11] and weak links [10,13] finding consistently ε ∼ −1 at low temperature, while BCS theory predicts ε > 0 [4,35]. As shown in Appendix A the exponential regularization gives ε ≈ −1/3, with the sign in agreement with experimental results.…”
Section: Phase-dependent Conductancementioning
confidence: 52%
See 1 more Smart Citation
“…The ratio ε between the PDC and the leakage conductance has been investigated in a number of experiments on tunnel junctions [8,12], point contacts [9,11] and weak links [10,13] finding consistently ε ∼ −1 at low temperature, while BCS theory predicts ε > 0 [4,35]. As shown in Appendix A the exponential regularization gives ε ≈ −1/3, with the sign in agreement with experimental results.…”
Section: Phase-dependent Conductancementioning
confidence: 52%
“…The measured value of the PDC in tunnel junctions [8,12], point contacts [9,11] and weak links [10,13,14] can not be explained by BCS theory. Several effects that can account for the discrepancy have been discussed in Ref.…”
Section: Introductionmentioning
confidence: 74%
“…The ratio ε has been investigated in a number of experiments on tunnel junctions [11,12], weak links [13,14], and point contacts [15,16], consistently finding ε ∼ −1 at low temperatures in disagreement with BCS theory which predicts ε > 0. This discrepancy may be accounted for by including frequency broadening in the BCS result [4] as we have done with the exponential factors in equations (4) and (5).…”
Section: Phase-dependent Conductancementioning
confidence: 99%
“…BCS theory cannot account for the measured value of the PDC in tunnel junctions [11,12], point contacts [13,14] or weak links [15][16][17]. Several effects may account for such discrepancy (see, e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%
“…One of them, the famous cos ϕ problem [7,8], puzzled the scientific community for many decades. Various experiments of the time [9][10][11][12][13][14] observed the sign of phase-dependent dissipative current, also known as the "cosine" or quasiparticle-pair interference term, to disagree from the prediction of the MTT [15]. It was later suggested that, in fact, either sign is possible, while the disagreement between the theory and experiments can be explained by broadening mechanisms which result in smearing of the Riedel peaks [16,17].…”
Section: Introductionmentioning
confidence: 99%